Risk factors of intrauterine fetal death: a case control study at the maternity of Yaoundé Central Hospital - Momo, Romaric Joel Tetsiguia; Fouedjio, Jeanne Hortence; Fouelifack, Florent Ymélé; Mbu, Robinson Enow (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine fetal death (IUFD) is the death before the beginning of the work of the fetus from the 28th week of pregnancy or a fetus of weight greater than or equal to 1000g. It occurs in 98% in poor countries, particularly in sub-Saharan Africa. The aim of this study was to identify the risk factors for IUFD in low-income countries. Methods: All the women with preeclampsia from 30 weeks onwards were enrolled in the study. The umblical artery (UA) Systolic-diastolic (S/D) ratio >2 standard deviation (SD) or UA-pulsatility index (PI) and UA-resistive index (RI) >2 SD were taken as abnormal. The middle cerebral artery (MCA) was visualised and cerebroumblical PI ratio calculated. MCA-RI<2SD was taken as abnormal. Results: Independent risk factors for IUFD are age over 30 years (ORa = 2.1, P = 0.052), (ORa = 2.4497, p = 0.01), household occupation (ORa = 2.0097, p = 0.0282), hypertension disorders (ORa = 2.11, p = 0.0176), antepartal haemorrhage (ORa = 3.9635, p = 0.000), multiparity (ORa = 13.3089, p = 0.0056). Conclusions: The main risk factors for IUFD identified in our study are maternal age greater than 30 years, hypertension, antepartal haemorrhage, multiparity, and the household profession. Any pregnant woman who has one of these factors should be follow-up closely during pregnancy with a weekly assessment of fetal well-being by the 28th week.